THE ANALYSIS OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON BEAUTY CLINIC CARE (THE CASE STUDY OF MIRACLE AESTHETIC CLINIC IN MANADO) - Tambingon, Lisa L.; Saerang, David P.E (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract : The fast growth of beauty clinic happens everywhere so it is brought The Researcher to research the problem, can beauty clinic give satisfaction for the customer through the service quality of the clinic. Beauty and women are two things are interrelated. The emergence beautiful construction that it has a white face, clean, and free of acne is an incentive for beauty clinics to provide services or beauty services. To know the relation between Service Quality and Customer Satisfaction on Miracle aesthetic clinic in Manado. The result is the service quality of Miracle Aesthetic Clinic Manado brought satisfaction to the customers because the informants of this study agreed that the employees also always deliver best feedback to their customers about the improvement of the beautification of their skin. For the clinic, this study recommends to maintain the availability of product like face cream because the number of customers are not equal with the number of products available. The general facility such as the availability of water in the toilet should be well maintained because this facility is important to complete comprehensive service quality.Keywords: service quality, customer satisfaction, beauty clinic careÂ